Exploring the Effect of a Cultural Gap on the Process of Absorbing Business Knowledge - Hirose, Yayoi (Cultural Arts Research and Development, 2022)
This study explores the implications of the difference between Japanese and Anglo-American cultures when Japanese organizations try to absorb business knowledge generated in Anglo-American culture. It relies on Todorova & Durisin’s model of Absorptive Capacity (2007) which allows for multi-level, individual, group, and organizational levels of absorption in the process of incorporating external knowledge. It compares four cases of Japanese organizations, who sought to absorb business knowledge that could change conventional Japanese management style by introducing one of two alternative Anglo-American developmental learning methods. The study identifies some specific cultural impediments and enablers for Japanese people trying to absorbing Anglo-American business knowledge, and suggests how the impediments can be overcome, by making structural and leadership changes during the introduction of the learning activities. The research explores whether and how 43 participants who experienced one or the other learning method transformed from a mind-set dominated by Japanese cultural norms and values to one that can both recognise the benefits of Anglo-American management thinking and translate it into changed practice. Whilst Todorova and Durisin’s model does not capture the way cultural difference affects the absorbing process, the results show that the differences between Japanese and Anglo-American cultural values, in terms of collectivism vs individualism, high-context vs low-context cultures, and power relationships affect progress through the phases of absorption. Thus, the study discusses the gradual process how Japanese individuals and organizations absorbed the Anglo-American knowledge by overcoming cultural differences.